Dynamics of Legitimation in Regional Organisations: The OAS and Non State Actors. Issue 4 (1st October 2020) - Mace, Gordon
ABSTRACT: Legitimation has been conceived mostly as an exercise in justification by international/regional organisations needing to convince audiences of the rightfulness of their behaviour. What we could call the external dimension of legitimation. The internal dimension, what happens between an organisation and its stakeholders, remains understudied. Analysing internal legitimation practices becomes important in the context of the opening-up of international organisations. Aside from the EU, however, evidence is still lacking as to the nature and extent of this opening-up, and the role of non-state actors (NSAs) in this context. The article seeks to fill part of this void using the OAS as a case study. It examines actors' practices during three central moments in the legitimation process. At each stage, OAS' legitimation-seeking practices and NSAs' legitimation/de-legitimation practices are analysed. The study reveals that NSAs have responded positively to the opening-up by the OAS despite tensions among member States.